The Effect of Taraxacum officinale Hydroalcoholic Extract on Blood Cells in Mice - Mehrdad Modaresi; Narges Resalatpour (Advances in Hematology)
Objectives. Dandelion (Taraxacum officinale) is a herbaceous perennial plant of the family Asteraceae and has medicinal and culinary uses. Dandelion has been used as a remedy for anemia, purifing the blood, and providing immune modulation. Therefore, the aim of this study was to investigate the effect of hydro alcoholic extract on blood cells in mice. Methods. Five groups each including ten adult female (Balb/C) mice weighing 30 ± 5 g were chosen. Normal saline was administered as placebo for group, and dandelion hydro alcoholic extract in doses of 50,100, and 200 mg/kg was injected intraperitoneally for 20 days to test groups and the last group was control group.WBC, RBC, HB, HCT, platelet, and other cells were measured with automated cell counter. Main Results. The number of RBC and the rate of HB in three doses of 100 and 200 mg/kg significantly increased (𝑃<0.05). As compared with control group, the number of WBC in three doses of 50, 100, and 200 mg/kg increased, but it was significantly in 200 mg/kg dandelion treated group as compared with control group(𝑃<0.05). The rate of platelet in three doses of 50, 100 and 200 mg/kg significantly decreased as compared with control group (𝑃<0.01). 3 doses of dandelion increased lymphocyte numbers significantly compared with controls. Conclusion. The study indicates efficacy of dandelion extract on RBC and HB in doses of 50, 100, and 200 mg/kg and in 200 mg/kg on WBC to achieve normal body balance.